2020
DOI: 10.3390/nano10020240
|View full text |Cite
|
Sign up to set email alerts
|

Protein Corona Composition of Silica Nanoparticles in Complex Media: Nanoparticle Size does not Matter

Abstract: Biomolecules, and particularly proteins, bind on nanoparticle (NP) surfaces to form the so-called protein corona. It is accepted that the corona drives the biological distribution and toxicity of NPs. Here, the corona composition and structure were studied using silica nanoparticles (SiNPs) of different sizes interacting with soluble yeast protein extracts. Adsorption isotherms showed that the amount of adsorbed proteins varied greatly upon NP size with large NPs having more adsorbed proteins per surface unit.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 72 publications
3
22
1
Order By: Relevance
“… 52 It was previously demonstrated that binding selectivity in SiO 2 NPs was independent of their particle size. 53 These findings strengthen the hypothesis that the nanotopography parameters studied herein may play a dominant role in the selective binding of protein during the formation of a corona. In the context of interaction with blood plasma proteins, the binding selectivity of NPs has been previously demonstrated, where blood-circulating lipid-based NPs displayed a protein pattern differing from that found in blood plasma without NPs.…”
Section: Resultssupporting
confidence: 83%
“… 52 It was previously demonstrated that binding selectivity in SiO 2 NPs was independent of their particle size. 53 These findings strengthen the hypothesis that the nanotopography parameters studied herein may play a dominant role in the selective binding of protein during the formation of a corona. In the context of interaction with blood plasma proteins, the binding selectivity of NPs has been previously demonstrated, where blood-circulating lipid-based NPs displayed a protein pattern differing from that found in blood plasma without NPs.…”
Section: Resultssupporting
confidence: 83%
“…On the contrary, proteins with a strong internal stability (“hard proteins”) tend not to contribute to adsorption and, when they do, not to undergo any significant structural rearrangements. In more recent years, statistical comparative analyses ,, revealed that the main physicochemical factors relevant to protein adsorption on silica NPs include (i) an enrichment in positively charged amino acids, particularly in arginine residues (forming electrostatic interactions with the negatively charged silica surface), and (ii) an enrichment in disordered regions and conversely a depletion in structured regions, confirming the hard/soft protein paradigm in the case of silica NPs.…”
mentioning
confidence: 92%
“…A recent report established a comprehensive list of factors that have been shown to govern protein adsorption on NPs . These factors are linked to the intrinsic properties of the NPs, the adsorbed proteins, and the characteristics of their suspending medium, drawing the three sides of the nanobio interface triangle. Among all of these physicochemical factors, some have been extensively studied, such as the size/curvature effect of NPs, the physicochemical properties of protein sequences, and the pH effect of the surrounding environment. Others have not been as thoroughly examined but may prove crucial under specific conditions (e.g., NP roughness, dynamic flow, and temperature). …”
mentioning
confidence: 99%
“…Conclusively, NPs surface curvature strongly affects the protein adsorption as protein-binding affinities are different for the bulk material and NPs surface. Thus, corona formed on NPs made of the same material differ in composition 57 . Undoubtedly, PC formation is a continuous process with changes in PC composition with time due to the motion of already adsorbed proteins which may be replaced by other proteins having stronger binding affinities until the process reaches an equilibrium which is known as the "Vroman effect" 58 .…”
Section: Impact Of the Size Of Npsmentioning
confidence: 99%